Efficient statistical methods for inference and model selection in diffusion-weighted MRI models - Mott, Lisa (2016)
Diffusion-Weighted Magnetic Resonance Imaging (DW-MRI) on the brain is a revolutionary method that provides in-vivo access to tissue macrostructure non-invasively (Basser et al., 1994). Recently, DW-MRI has been shown to have great potential in characterising brain microstructure, such as diameter and size distribution of neuronal fibres, features that were available so far only postmortem or through animal studies (Zhang et al., 2011). Using a process known as Tractography the existence of brain connections can be estimated using a set of DW images (Basser et al., 2000).